Cohesion Policy and environmental protection: The attitude of Polish public organisations - Herodowicz, Tomasz (Quaestiones Geographicae, 2023)
The quality of public organisations, which is highly dependent on the institutional quality, is one of the fundamental factors determining policy effectiveness and socio-economic growth trajectories in a long-term perspective. The article provides an insight into the topic of the informal institutions characterising Polish public organisations by paying special attention to informal institutions referring to the awareness of the need for sustainability and an attitude towards Cohesion Policy implementation in the field of environmental protection. Therefore, the main research goal was to verify the following hypothesis: “The staff of Polish public organisations are characterised by the awareness of the need for sustainability and a positive attitude towards Cohesion Policy implementation in the field of environmental protection”. To this end, a direct research technique (e-questionnaire) involving representatives of organisations responsible for Cohesion Policy implementation and for natural environment protection was applied. This made it possible to gather unique data and to elaborate the structure indicators describing the beliefs of staff employed in public organisations. Overall, their positive attitude towards the directions and assumptions of Cohesion Policy in the field of environmental protection was proved. The examined groups of organisations were characterised by a similar way of thinking about Cohesion Policy funds as an environmental protection factor, which seems to be an important institutional building block affecting Cohesion Policy effectiveness. Some of the respondents demonstrated critical thinking, and they developed their own ideas regarding the most important environmental protection factors including mainly both formal and informal institutional elements, such as legal regulations or ecological education.